2012
DOI: 10.1093/ejo/cjs016
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane and non-Cochrane systematic reviews in leading orthodontic journals: a quality paradigm?

Abstract: The aims of this study were to assess and compare the methodological quality of Cochrane and non-Cochrane systematic reviews (SRs) published in leading orthodontic journals and the Cochrane Database of Systematic Reviews (CDSR) using AMSTAR and to compare the prevalence of meta-analysis in both review types. A literature search was undertaken to identify SRs that consisted of hand-searching five major orthodontic journals [American Journal of Orthodontics and Dentofacial Orthopedics, Angle Orthodontist, Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 13 publications
4
72
2
1
Order By: Relevance
“…However, an established threshold for assigning descriptive quality or an overall quality score has not yet been established; therefore, a Bhigher^AMSTAR score, rather than a Blower^AMSTAR score, may help to reveal methodologically sound systematic reviews. Conversely, we identified some selected reviews, which showed that 20 % of included SR satisfied nine or more of the 11 AMSTAR criteria [17,18]. While it was out of the scope of this review to explore reasons for differences in methodological quality of SR across dental disciplines, the present results may serve as reference for further methodological development of SR published in these fields.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, an established threshold for assigning descriptive quality or an overall quality score has not yet been established; therefore, a Bhigher^AMSTAR score, rather than a Blower^AMSTAR score, may help to reveal methodologically sound systematic reviews. Conversely, we identified some selected reviews, which showed that 20 % of included SR satisfied nine or more of the 11 AMSTAR criteria [17,18]. While it was out of the scope of this review to explore reasons for differences in methodological quality of SR across dental disciplines, the present results may serve as reference for further methodological development of SR published in these fields.…”
Section: Discussionmentioning
confidence: 92%
“…The three least common topics were restorative dentistry (n=15; 2.3 %), pain (n=11; 1.7 %), and other unclassified studies (n=25; 3.9 %). Although the median number of studies per SR was [15][16][17][18][19][20][21][22][23][24][25][26][27][28], the majority (70.2 %, n=450) included fewer than 24 studies in their review, while 2.0 % (n=13) included more than 100 studies. Most studies failed to describe study characteristics (88.2 %, n = 567), with terms such as Badults^(6.5 %, n = 42) or Bpaediatrics^(5.3 %, n = 34) populations used sparingly among the studies.…”
Section: Description Of Studies Meeting Our Inclusion Criteriamentioning
confidence: 99%
“…10 Most reviews were published in AJODO (31.2%), in Angle Orthodontist (29.4%), and on the CDSR (23.9%). In terms of adherence to individual criteria, the overall performance was assessed as good for reporting of the abstract, explanation of rationale for the review, listing of information sources and criteria for study selection, analysis of risk of bias (or quality) of primary studies, presentation of results from individual studies, summary of the evidence, and reporting of both limitations and conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…Discrepancies between the authors in the grading of individual criteria were resolved by joint discussion. AMSTAR scores for the included studies have been reported in a prior study 10 ; in this study, the relationship between overall reporting (PRISMA) and quality (AMSTAR) scores for each review was to be assessed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation